Panel Granger causality between financial development and economic growth - Ferreira, Cândida (2021)
This paper uses panel Granger causality estimations with the approaches developed by Nair-Reichert and Weinhold (2001), and Bangake and Eggoh (2011) as well as the Dumitrescu and Hurlin (2012) test, with the algorithm developed by Lopez and Weber (2017), to analyse the causality relations between all the nine IMF financial development indices, and the real GDP growth considering a sample of 46 countries spread by all continents over the interval 1990- 2017. The results obtained reveal the dynamic character of these causality relations and overall, no significant differences were found when comparing the results obtained for the financial institutions indices with those regarding the financial markets indices. The results confirm the existence of bidirectional causality, although not with the same statistical robustness for all the IMF indices, addressing relevant aspects of the financial development: access, depth and efficiency of the financial institutions and markets.